Transthoracic sonographic scores in evaluating the success of different scelerosing modalities in patients with malignant pleural effusion - Gamal Agmy; Mohamed F. Adam; Safaa Ahmed El Sagheir; Manal A. Mahmoud (The Egyptian Journal of Bronchology, 2022)
Abstract Background Malignant pleural effusions (MPE) mostly arises from metastases to the pleura from other sites. Management of malignant effusions aims to palliate dyspnea and prevent the reaccumulation of pleural fluid to improve patients’ quality of life. Pleurodesis is the most common palliative treatment for patients with refractory MPE. This study was carried out to evaluate the performance of transthoracic sonographic (TUS) scores (pleural sliding and pleural adherence score) in predicting the success of pleurodesis by different modalities in patients with malignant pleural effusion. One hundred malignant pleural effusion patients were enrolled to an interventional clinical trial from September 2019 to April 2021 for palliative management of dyspnea. Pleurodesis for palliative treatment of dyspnea was done either spontaneously by the intercostal chest tube or by a sclerosing agent such as tetracycline solution or tetracycline poudrage or iodopovidine. Patients were randomly allocated to one of these four groups where each group included 25 patients. Transthoracic ultrasound was performed at baseline, and 1 month after pleurodesis and the lung sliding score and pleural adherence score were evaluated. Results Majority of patients (78%) had high baseline lung sliding score (7-8). Post pleurodesis only 11.4% had high scores (p<0.001), also the mean lung sliding score decreased significantly in comparison to the baseline values (p˂ 0.001) in the spontaneous, tetracycline solution, tetracycline poudrage, and iodopovidine groups (7.04 ± 1.02 vs. 4.85 ± 1.60, 7.28± 0.98 vs. 4.48± 1.75, 7.20±0.96 vs. 4.44 ± 1.45, 7.04±0.93 vs. 3.35±1.81, respectively). Iodopovidine pleurodesis group in comparison to the other modalities showed the highest pleural adherence score (12.64 ± 2.98) and absent lung sliding in 72.7% of cases and 70 % success rate. Pleural adherence score at cut off ≥ 12 showed 92.75% sensitivity, 89.47% specificity, 92.1 accuracy, and 0.911 area under the curve (AUC) for predicting successful pleurodesis. Conclusion TUS scores is a feasible, bedside, and accurate method to detect the outcome of pleurodesis. Iodopovidone was more effective than tetracycline solution, tetracycline poudrage, and spontaneous pleurodesis. Trial registration ClinicalTrials.gov. NCT04074902. Registered on 29 August 2019